Prevention of Periprosthetic Joint Infection: What Are the Effective Strategies? - Alijanipour, Pouya; Heller, Snir; Parvizi, Javad (The Journal of Knee Surgery, 2014)
Periprosthetic joint infection (PJI) following total knee arthroplasty is a major burden for patients and health systems. Prevention of this challenging complication through implementation of effective strategies should be a priority. These strategies should encompass various levels of patient care. Multiple modifiable risk factors such as uncontrolled hyperglycemia, obesity, smoking, substance abuse, and nasal colonization with Staphylococcus aureus have been described for PJI. Preoperative recognition and mitigation of these risk factors along with optimization of nonmodifiable risk factors such as kidney, liver, or immune system insufficiency can considerably decrease the risk of PJI. A comprehensive perioperative protocol should involve optimization of the operative environment to reduce the number of bacteria and particulates in the air. Several surgical and nonsurgical details of intraoperative care such as maintenance of normothermia, skin preparation, surgical field irrigation, wound closure, and duration of surgical and anesthetic procedure can influence the occurrence of PJI. Prophylactic perioperative antibiotic administration is probably one of the most important strategies in preventing PJI. Implementation of surgical safety checklist can diminish the risk of perioperative complications, particularly surgical site infection. Controversy regarding efficacy, efficiency, and optimization of some preventive measures continues to exist due to inconsistency or inadequacy of available evidence. Novel research has focused on designing PJI-resistant implants and developing vaccines that target molecule components with major role in the process of bacterial adhesion to the implant or periprosthetic tissues.
Keywords: periprosthetic joint infection; surgical site infection; total knee arthroplasty; prevention